2008
DOI: 10.1093/cvr/cvn226
|View full text |Cite|
|
Sign up to set email alerts
|

Cilostazol inhibits cytokine-induced nuclear factor- B activation via AMP-activated protein kinase activation in vascular endothelial cells

Abstract: In the light of these findings, we suggest that cilostazol might attenuate the cytokine-induced expression of adhesion molecule genes by inhibiting NF-kappaB following AMPK activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 24 publications
5
40
2
Order By: Relevance
“…Otsuki et al 8) reported that cilostazol repressed vascular cell adhesion molecule-1 gene transcription in cultured HUVEC by inhibiting NF-B binding to its recognition sequence. Recently, Hattori et al 25) documented that cilostazol inhibited cytokine-induced NF-B activation via AMP-activated protein kinase activation in HUVEC; however, our results indicated that cilostazol failed to affect the cytokine-induced accumulation of STAT1 and NF-B in HUVEC nuclei.…”
Section: Discussioncontrasting
confidence: 87%
“…Otsuki et al 8) reported that cilostazol repressed vascular cell adhesion molecule-1 gene transcription in cultured HUVEC by inhibiting NF-B binding to its recognition sequence. Recently, Hattori et al 25) documented that cilostazol inhibited cytokine-induced NF-B activation via AMP-activated protein kinase activation in HUVEC; however, our results indicated that cilostazol failed to affect the cytokine-induced accumulation of STAT1 and NF-B in HUVEC nuclei.…”
Section: Discussioncontrasting
confidence: 87%
“…20 Therefore, cilostazol not only inhibits platelet aggregation 20 but also has favorable pleiotropic effects on the diverse processes in preclinical studies. [22][23][24] Adjunctive cilostazol can reduce aspirin and clopidogrel resistance in patients with vascular disease 18,19,43 Cilostazol not only can inhibit oxidative stress and inflammatory burden 23,44 but also can protect from endothelial senescence and dysfunction. 22,24 Enhancement of endothelial nitric oxide synthase by cilostazol underlies its vasodilating property, 22 which is used for intermittent claudication and cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…20 Unlike other antiplatelet agents, cilostazol not only inhibits platelet aggregation 20 but also has favorable pleiotropic effects on neointimal hyperplasia after PCI 21 and the diverse processes of atherosclerosis. [22][23][24] Furthermore, cilostazol is mainly converted into the active metabolites by the CYP3A system, 25 which might imply less impact of the CYP2C19 mutant allele for additive platelet inhibition with cilostazol.…”
Section: Clinical Perspective On P 459mentioning
confidence: 99%
“…It has even been proposed that the vascular consequences of the hypo-adiponectinemia associated with atherosclerosis and diabetes may be circumvented by agents that increase AMPK activity. 150 A number of compounds are reported to activate the AMPK in endothelial cells and improve endothelium-dependent relaxation, including the selective inhibitor of phosphodiesterase 3 cilostazol, 65,151 fenofibrate, 64,152,153 and rosiglitazone. 28 Polyphenols such as resveratrol also increase phosphorylation of AMPK 154 and improve the survival of mice on a high-calorie diet.…”
Section: Fisslthaler and Fleming Ampk In Endothelial Signaling 121mentioning
confidence: 99%